(untitled) (The Scientific Journal of University of Saba Region, 2026)
This study examines a scholarly figure of profound influence in the Yemeni context: the distinguished judge and scholar Muhammad bin Ismail Al-Imrani (may Allah have mercy on him). Specifically, it investigates his fatwas and his methodology of issuing fatwas (iftā’). The study begins with a brief biography of the Shaykh, followed by an overview of the state of fatwa issuance in Yemen, highlighting the weaknesses and deficiencies that uniquely characterize it compared to most other countries. The heart of the study is found in the third section, which analyzes Al-Qadi Al-Imrani’s fatwa methodology, addressing both his personal attributes and his methodological approach. Among the most important personal characteristics of the Shaykh explored by the study are: humility and accessibility; refusal to accept monetary compensation for fatwas; written documentation; energy and dedication in fatwa issuance; shrewdness in detecting questioners’ tricks and deceptions; ability to understand diverse modes of expression; use of traditional communication means; and gentleness and kindness. Regarding methodological features, the study examines: the influence of Al-Shawkani’s school and the broader ijtihad school in Yemen; reliance on textual evidence and rejection of sectarian fanaticism; consideration of Yemeni law and court practices; simplicity and ease in formulating answers; flexibility and facilitation (taysīr); attention to sectarian differences; and avoidance of political controversies, with examples provided for most features. The study also addresses the sources and locations where the Shaykh’s fatwas may be found, dedicating a final subsection to this purpose, while noting the significant deficiency in collecting and documenting them to date, and the limited efforts made in this regard. The study employed a descriptive analytical methodology. It concludes with several recommendations, among which are: the urgent need to collect the Shaykh’s fatwas from their various sources and compile them into a comprehensive encyclopedia befitting his scholarly legacy.